Governance Scorecards as Tools for Breakthrough Results - Estanislao, Jesus P (World Bank, Washington, DC, 2012)
Governance has become a mantra for doing the good and proper things. In public life, it has become more than a mini-rage: when things fail, a failure of governance is brought up as the explanatory variable; and good governance is presented as the alternative pathway to success. In the private sector, corporations are given ratings for the propriety of their governance practices: presumably, those that receive high ratings are governed well and can become the recipients of high market approval ratings, while those at the lower end of the ratings scale are to be dealt with as high-risk enterprises. If good governance does lead to good breakthrough results, it is well worth to look more closely at what governance entails and in what way this may lead to higher levels of performance that brings about desirable results. The authors do need to get down from merely repeating governance as a mantra and into actually observing, as much as possible in day-to-day operations and actions, the discipline of governance. The authors do need to meet the fundamental governance challenge, which is to connect the values that aspire to hold and the actions the authors need to undertake so as to give flesh and substance to those values. The challenge is, indeed, how to walk the talk about governance.